PENGARUH PERTUMBUHAN MIKROBA TERHADAP MUTU KECAP SELAMA PENYIMPANAN (The influence of growth of microbes on soy sauce quality during storage) - Henky Isnawan Hendritomo (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
This investigation conducted was to study the influence of growth of microbes on soy sauce quality during storage. The time of storage was as follows 1, 90 and 180 days. The determinations consisted of sucrose, protein, and sodium chloride content and total microbes such as molds and bacteria. The result showed that the sucrose content was 67,8% and protein content was 3,07%. After 6 months storage the sucrose and protein content decreased respectively from 67.8% to 58,8% and from 3.07% to 2,36%. The quantity of bacteria and molds increased respectively from 2100 to 3700 colony/ml and from 400 to 6100 colony/ml.